RANCANG BANGUN SISTEM INFORMASI PADA SD NEGERI 17 PRABUMULIH BERBASIS WEB - iwan setiawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Computerized systems have become commonplace, seeing the development of technology in Indonesia at this time. The system for registration, processing grades and teacher attendance at SDN 17 Prabumulih is still manual. So that sometimes it causes ineffectiveness and frequent mistakes. Therefore, a computerized information system is made so that the registration process, processing student grades and attendance of teachers and TU staff at SDN 17 Prabumulih can be carried out optimally. The method proposed in making this system is the Prototype Development method using the Unified Modeling Language (UML) as the modeling language using PHP as the program and MySQL as the database. With this information system, prospective new students can register online, processing student grades and computerized teacher attendance and TU staff.